Squamous Cell Carcinomas of the Head and Neck Cancer Response to Programmed Cell Death Protein-1 Targeting and Differential Expression of Immunological Markers: A Case Report - Merhi, Maysaloun; Raza, Afsheen; Inchakalody, Varghese Philipose; Nashwan, Abdulqadir Jeprel Japer; Allahverdi, Niloofar; Krishnankutty, Roopesh; Uddin, Shahab; Zar Gul, Abdul Rehman; Al Homsi, Mohammed Ussama; Dermime, Said (Frontiers in Immunology, 2018)
Targeting the PD-1/PD-L1 pathway has been shown to enhance T cell-mediated anti-tumor immunity. Clinical responses are limited to subgroups of patients. The search for biomarkers of response is a strategy to predict response and outcome of PD-1/PD-L1 checkpoint intervention. The NY-ESO-1 cancer testis antigen has been considered as a biomarker in head and neck squamous cell carcinoma (HNSCC) patients and can induce both specific NY-ESO-1 antibody and T cells responses. Here, we correlated clinical responsiveness to anti-PD-1 (nivolumab) treatment with immunity to NY-ESO-1 in a patient with recurrent HNSCC. The patient was treated with second-line treatment of nivolumab and had a stable disease for over seven months. His NY-ESO-1 antibody was found to be lower after the 3rd (****p<0.0001) and the 5th (****p<0.0001) cycles of treatment compared to base line, and this was in line with the stability of the disease. The NY-ESO-1-specific T cells response of the patient was found to be increased after the 3rd and the 5th (**p=0.002) cycles of treatment but had a significant decline after progression (**p=0.0028). The PD-1 expression by the patient’s T cells was reduced 15-folds after nivolumab treatment and was uniquely restricted to the CD8+ T cells population. Several cytokines/chemokines involved in immune activation, were upregulated after nivolumab treatment; two biomarkers were reduced at progression (IL-10: ****p<0.0001 and CX3CL1: ****p<0.0001). On the other hand, some cytokines/chemokines contributing to immune inhibition, were downregulated after nivolumab treatment; two biomarkers were increased at progression (IL-6: ****p<0.0001 and IL-8: ****p<0.0001). This data support the notion that the presence of anti-NY-ESO-1 integrated immunity and some cytokines/chemokines profile may potentially identify a response to PD-1 blockade in HNSCC patients.